Investor Protection: A Juridical Review Of Capital Market Manipulation - Khomaini Khomaini (International Journal of Science and Environment (IJSE), 2025)
Market manipulation is a phenomenon that harms market integrity and investor confidence, so a comprehensive legal protection mechanism is needed. The study aims to analyze legal arrangements related to the practice of market manipulation and identify the forms of legal protection available to investors who become victims of manipulation. Using the normative legal research method, this study relies on the analysis of primary, secondary, and tertiary legal materials to examine the formal juridical aspects of the problem. The results show that market manipulation is an act of creating a false picture of trading activity or securities prices on the exchange, which is carried out by certain parties to influence securities prices or disseminate inaccurate and misleading information. Legal protection of investors can be pursued through two main approaches: preventive protection in the form of investor education and transaction supervision by the Financial Services Authority (OJK), and repressive protection which includes litigation, non-litigation dispute resolution mechanisms, and the application of sanctions against market manipulation perpetrators.